Human Resource Management In Special Education - Lantang, Dani; E M Sumual, Tinneke; Jeini Usoh, Elni; Robert Tuerah, Paulus; D M Sumual, Shelty (Pusat Publikasi Nusantara, 2023)
Human resources need to be managed properly so that they can play a role in accordance with their functions. That is why there is a need for human resource management. Human resource management is a process related to the implementation of human resource management or management functions which are directly handed over to the school education unit to be developed in accordance with the potential possessed by the school. The scope of human resource management includes: employee planning; employee procurement; employee coaching and development; promotion and mutation; dismissal of employees; compensation, and employee assessment. All of that needs to be done properly and correctly so that what is expected can be achieved